Performans Reproduksi Sapi Peranakan Simmental (Psm) Hasil Inseminasi Buatan di Kabupaten Sukoharjo Jawa Tengah - Iswoyo, Iswoyo; Widiyaningrum, Priyantini (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
Information of performance reproduction crossed result of cow in ranch was immeasurable enough because  condition  of  its  different  conservancy.  This  research  aimed to  know  difference  of reproduction performances of  Simmental Crossed Cow (PSM)  result  of  Artificial  Insemination  (AI)  looked  after  by farmer  of  breeder  of  Group  Farmer  Livestock  member  (KTT)  and  non member  of  KTT in District of Sukoharjo.  Research  conducted  with  method  of  survey  by  means  of  questionaire.  Determination  of research  sample arranged purposive sampling.    Variables  were perceived  to  cover  pregnant  time  depth, service period, calving interval, non return rate and service per conception. Data had been analyzed with Z  test  or  presented  descriptively.  Results  of  this  research  indicated  that  difference  of  breeder  status (member  of  KTT  and  non  KTT)  giving  different  influence  in  conservancy.  Statistical  analysis  result  of research successively indicated that gestation period mean of PSM cow property of member of KTT and non member of KTT did not differ reality (KTT 301.82 ± 29.93 day; non KTT 308.5 ± 33.73 day); service period differ  reality  (KTT  110.89  ±  30.23  day;  non  KTT 114.11  ±  56.78  day).  Calving  interval  differ reality  (KTT  392.28  ±  77.27  day,  non  KTT  416.02  ±  64.63  day);  non  return rate differ  reality  (KTT 87.72 ± 11%; non KTT 79.53 ± 18%); service per conception do not differ reality (KTT 1.12 ± 0.32; non KTT  1.19  ± 0.40.  This  research  concluded that  performance reproduction of  PSM cow looked  after  by breeder of member of KTT better in general compared to cow of PSM looked after by is breeder non KTT